Why some potentially effective staffing practices are seldom used. - Terpstra DE; Rozell EJ (Public Personnel Management)
The purpose of this study was to identify the reasons why some organizations do not employ certain HRM practices that could increase levels of employee performance and organizational profitability. The focus was on the staffing area (recruitment and selection) of HRM Specifically, this study looked at five staffing practices that the academic research literature has found can significantly increase employee performance levels. Descriptions of these practices, and references supporting their impact on employee performance, are provided in Exhibit 1.